200k views
1 vote
What is the product?

What is the product?-example-1
User JamesL
by
5.7k points

2 Answers

2 votes
(x-1)(6x-1) is your answer!
User Bompf
by
4.8k points
3 votes

For this case we must find the product of the following expression:


6 (x ^ 2-1) * \frac {6x-1} {6 (x + 1)}

We know that:


(x ^ 2-1) = (x + 1) (x-1)

Applying distributive property can be demonstrated:


(x + 1) (x-1) = x ^ 2-x + x-1 ^ 2 = x ^ 2-1

We rewrite the given expression:


6 (x + 1) (x-1) * \frac {6x-1} {6 (x + 1)} =\\\frac {6 (x + 1) (x-1) (6x-1)} {6 (x + 1)} =

We cancel similar terms:


(x-1) (6x-1)

Answer:

Option D

User German Alzate
by
4.3k points